Pengaruh Kualitas Pelayanan dan Sanksi Perpajakan Yang Diberikan Fiskus Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Kasus Kantor Pelayanan Pajak (KPP) Pratama Padang Satu) - Ingra Sovita; Aulia Ramadhani Hayati (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2019)
This study aims to determine the effect of Service Quality and Tax Sanctions given by the Fiscal Authority on the Compliance of Individual Taxpayers (Case Study of the Pratama Tax Service Office in Padang Satu. This study uses an independent variable (X) including Service Quality of Fiscal (X1), Sanctions Taxation (X2) and the dependent variable (Y), namely Personal Taxpayer Compliance The population in this study were all individual taxpayers at the Pratama Padang Satu Tax Service Office (176.240). The results obtained from this study indicate variable Service Quality with Determination R2 value of Adjusted R2 of 0.786 or 78.6% which affects the compliance of Taxpayers while the remaining 21.4% is influenced by other variables not examined in this study. In fact, the Fiscal Service Quality variable has a positive and significant effect on Taxpayer Compliance with a significant value (0.039), while the Tax Sanction variable has a positive and significant effect on Taxpayer Compliance with a significant value (0.023). Service Quality Variables and Tax Sanctions that are given Simultaneous Fiscus have a positive influence on the Compliance of Individual Taxpayers, showing a calculated f value of 48,845 with a significance level of 0.000 <0.05